2023
DOI: 10.3390/su15118490
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Effect of Strategic Planning on the Relationship between Career Path Planning and Job Performance

Abstract: This study aimed to assess the moderating effect of strategic planning on the relationship between career path planning and job performance among employees in small and medium-sized enterprises (SMEs) in the Kingdom of Bahrain. A convenience sample consisting of 249 participants was selected. The study used SPSS and Smart-PLS to analyze the data. The findings of the study revealed that strategic planning and career path planning affected SME employees’ performance. In contrast, it was found that strategic plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…There is a clear relationship between higher organizational ratings and improved occupational health and safety (OHS) performance. This insight is consistent with previous studies such as [62,63]. The survey by [64] provided additional support for the above association, highlighting the existence of a moderately positive relationship between occupational health and safety (OHS) measures and operational efficiency within small and medium-sized enterprises (SMEs).…”
Section: Discussionsupporting
confidence: 89%
“…There is a clear relationship between higher organizational ratings and improved occupational health and safety (OHS) performance. This insight is consistent with previous studies such as [62,63]. The survey by [64] provided additional support for the above association, highlighting the existence of a moderately positive relationship between occupational health and safety (OHS) measures and operational efficiency within small and medium-sized enterprises (SMEs).…”
Section: Discussionsupporting
confidence: 89%
“…The process includes developing and implementing strategies for the organization's mission and objectives. Previous research has reported a significant association between the efficacy of strategic planning and enhanced organizational performance [3,28]. According to [29], when an organization diligently strategizes its resource allocation, determines critical objectives, and effectively responds to evolving market conditions, it tends to achieve superior performance compared to its competitors.…”
Section: Strategic Planning and Organizational Performancementioning
confidence: 99%
“…Strategy places a company, provides trade-offs, and coordinates activities [1,2]. An organization's strategy includes its goals, policies, and activities [3]. Strategic planning is proactive and future-facing, aligning the business with evolving marketing possibilities.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations